Pharmacotherapy in Stevens Johnson Syndrome and Toxic Epidermal Necrolysis: Intravenous Immunoglobulin, Systemic Corticosteroids, Cyclosporine or Tnf-Alpha Inhibitors? Sjs/Net Therapeutic Update [Farmacoterapia en el Síndrome de Stevens-Johnson y la Necrólisis Epidérmica Tóxica: ¿Inmunoglobulina Endovenosa, Corticoides Sistémicos, Ciclosporina O Inhibidores Tnf-Alfa? Actualización Terapéutica Ssj/Net] - Jeldres-Pulgar, A; Aedo-Inostroza, G (Ediciones Doyma, S.L., 2021)
[No abstract available]